Formação em direito e economia do mar - Sardinha, Álvaro Máximo Pacheco (2020)
This project represents a business initiative, whose mission consists on gathering the fundamental knowledge of the ocean, acquired in academy and continuous research, and promote its transmission to target audiences where it is valued and useful. It is no secret - the ocean will be an economic force this century, offering vast opportunities for employment, innovation and investment. The 21st century is already known as the blue century, given the growth potential of the sea economy. However, the development advocated depends on the level of knowledge of law and economy of the sea, a critical success factor for the use and sustainable exploitation of the ocean. The combination of ocean knowledge with human, scientific and financial resources, accelerates the growth of the sea economy. For this reason, it is a priority to promote the meeting of these factors. Perform law and economy of the sea training, in short-term and geographically mobile events, bringing the ocean and people closer together through knowledge, is an important key to inform and inspire blue careers, train professionals and attract investment. Communication of this business initiative is also considered a critical factor for its success, and particular importance is given to the development of a digital strategic communication plan.